Research of ERAWA-1 and ERAWA-2 Reactive Cassettes - Adam WIŚNIEWSKI (Problemy Mechatroniki, 2019)
In the paper there are presented general parameters of shaped charge projectiles (SC) and explosively formed projectiles (EFP), designed for destroying of armed vehicles, and parameters of explosive reactive armours (ERA), which significantly increase capability of protection of rolled homogeneous armour (RHA) against piercing by these projectiles. There are shown examples of destruction of tanks not protected by the ERA. Their parameters are presented on the base of ERAWA-1 and ERAWA-2 Polish reactive cassettes for PT-91 Hard tank. There are described the following requirements: capability of protection of ERAWA-1 and ERAWA-2 cassettes as a result of reaction in the static test of shaped charge projectiles PG-7 and 125 mm BK-14M, effect in the dynamic test of 125 mm BM-15 projectile that pierces through due to its kinetic energy, and resistance to detonation of the cassettes fired by 12.7×107 mm AP B-32 projectiles. There are demonstrated results of the resistance to detonation of the neighboring ERAWA cassettes in case of detonation of the central cassette in the panel.